Disrupted in schizophrenia 1 and phosphodiesterase 4B: towards an understanding of psychiatric illness - Millar, J Kirsty (Blackwell Publishing Ltd, 2007)
Disrupted in schizophrenia 1 (DISC1) is one of the most convincing genetic risk factors for major mental illness identified to date. DISC1 interacts directly with phosphodiesterase 4B (PDE4B), an independently identified risk factor for schizophrenia. DISC1–PDE4B complexes are therefore likely to be involved in molecular mechanisms underlying psychiatric illness. PDE4B hydrolyses cAMP and DISC1 may regulate cAMP signalling through modulating PDE4B activity. There is evidence that expression of both genes is altered in some psychiatric patients. Moreover, DISC1 missense mutations that give rise to phenotypes related to schizophrenia and depression in mice are located within binding sites for PDE4B. These mutations reduce the association between DISC1 and PDE4B, and one results in reduced brain PDE4B activity. Altered DISC1–PDE4B interaction may thus underlie the symptoms of some cases of schizophrenia and depression. Factors likely to influence this interaction include expression levels, binding site affinities and the DISC1 and PDE4 isoforms involved. DISC1 and PDE4 isoforms are targeted to specific subcellular locations which may contribute to the compartmentalization of cAMP signalling. Dysregulated cAMP signalling in specific cellular compartments may therefore be a predisposing factor for major mental illness.